The Implementation of Female Circumcision by Midwives in Aceh - Warahmah, Mawaddah; Nurjannah, Nurjannah; Hayati, Zinatul; Usman, Said; Saputra, Irwan (PT Inovasi Pratama Internasional, 2025)
The practice of Female Genital Mutilation (FGM), also known as female circumcision, is still maintained, especially in Aceh, despite being banned by the WHO and the government. This practice is not taught in the school, including the midwifery school, as midwives are among the healthcare providers who generally offer this service. The dynamics of policy changes and deeply rooted differences in religious and cultural views create confusion for midwives in the field, particularly given the still high demand and community encouragement. The purpose of this research was to analyse the factors influencing the implementation of female circumcision by midwives. This was a cross-sectional study with the population of midwives who were working in the Aceh Province region in 2024. The sample of this study consisted of midwives who provide female circumcision services in Aceh, with a sample size of 86 people. Statistical analysis used the Chi-Square test with the SPSS v.25 . The majority of midwives performed circumcision about 1-2 times a month, and midwives perceived circumcision as a social necessity. Midwives aged ≥ 43 years, with work experience ≥ 13 years, working for ≥ 20 years, possessing good knowledge, and having a positive attitude tended to perform risky circumcisions. The results of the statistical test indicated that there was no significant relationship between age, years of service, duration of providing female circumcision services, knowledge, attitude, and social needs regarding the implementation of female circumcision. The research results indicated that midwives in Aceh continue to practice female circumcision, with the majority performing it in a risky manner. Although midwives have positive knowledge and attitudes, social necessity factors are the main drivers in its implementation